An Effect of Ursodeoxycholic Acid on Inflammation, Steatosis and Liver Fibrosis and Atherogenesis Factors in Patients with Non-Alcoholic Fatty Liver Disease: Results of the USPEH Study - M. V. Mayevskaya; M. Yu. Nadinskaia; V. D. Lunkov; I. Yu. Pirogova; E. V. Chesnokov; Kh. B. Kodzoeva; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2020)
Aim. To evaluate effects of ursodeoxycholic acid (UDCA) on inflammation, steatosis and liver fibrosis and atherogenesis factors in patients with non-alcoholic fatty liver disease (NAFLD).Materials and methods. The study included 139 patients with NAFLD who received 15 mg/kg of UDCA (Ursosan®) per day for 24 weeks. Before and after the study, liver function and lipid metabolism, liver steatosis index FLI, intimamedia thickness (IMT) of the carotid arteries were determined. The cardiovascular risk was calculated according to the ASCVD 2013.Results. The use of UDCA in patients with NAFLD led to a decrease in ALT (p < 0.001), AST (p < 0.001) and GGT (p < 0.001) activity; total cholesterol concentration (p < 0.001); triglycerides (p < 0.001); and LDL (p < 0.001) in the blood and the FLI liver steatosis index (p < 0.001). In addition, the rate of cardiovascular risk (p = 0.022) and IMT (р = 0.048) in women also decreased.Conclusions. The use of UDCA in NAFLD reduces the activity of inflammatory processes in the liver, its steatosis, and also improves lipid metabolism and exerts potential anti-atherogenic effects. Against the background of UDCA administration, there was no progression of liver fibrosis. None of the participants in the observational programme reached a normal body mass by the end of the program; therefore, the attained positive changes should be attributed directly to the effects of UDCA.